Music-making and depression and anxiety before and during the COVID-19 pandemic: results from the NAKO cohort study in Germany - Becher, Heiko; Krist, Lilian; Menzel, Juliane; Fernholz, Isabel; Keil, Thomas; Kreutz, Gunter; Schmidt, Alexander; Streit, Fabian; Willich, Stefan N.; Weikert, Cornelia (International journal of public health, 2024)
Objectives: To investigate the association of musical activity with mental health during the COVID-19 pandemic. Methods: A total of 3,666 participants reported their musical activity before and mental health indicators before and during the pandemic. Depression was assessed with the Patient Health Questionnaire, anxiety with the Generalized Anxiety Disorder scale. The association between mental health scores and musical activities was investigated using linear regression. Results: Within the last 12 months, 22.1% of the participants reported musical activity (15.1% singing, 14.5% playing an instrument). Individuals with frequent singing as their main musical activity had higher scores before the pandemic than non-musicians and the worsening during the pandemic was more pronounced compared to non-musicians. Instrumentalists tended to have slightly lower scores than non-musicians indicating a possible beneficial effect of playing an instrument on mental health. Conclusion: The pandemic led to a worsening of mental health, with singers being particularly affected. Singers showed poorer mental health before the pandemic. The tendency for instrumentalists to report lower depression scores compared to non-musicians may support the hypothesis that music-making has a beneficial effect on health.